Whither the genus Caldicellulosiruptor and the order Thermoanaerobacterales: phylogeny, taxonomy, ecology, and phenotype - Bing, Ryan G.; Willard, Daniel J.; Crosby, James R.; Adams, Michael W. W.; Kelly, Robert M. (Frontiers in Microbiology, 2023)
The order Thermoanaerobacterales currently consists of fermentative anaerobic bacteria, including the genus Caldicellulosiruptor. Caldicellulosiruptor are represented by thirteen species; all, but one, have closed genome sequences. Interest in these extreme thermophiles has been motivated not only by their high optimal growth temperatures (≥70°C), but also by their ability to hydrolyze polysaccharides including, for some species, both xylan and microcrystalline cellulose. Caldicellulosiruptor species have been isolated from geographically diverse thermal terrestrial environments located in New Zealand, China, Russia, Iceland and North America. Evidence of their presence in other terrestrial locations is apparent from metagenomic signatures, including volcanic ash in permafrost. Here, phylogeny and taxonomy of the genus Caldicellulosiruptor was re-examined in light of new genome sequences. Based on genome analysis of 15 strains, a new order, Caldicellulosiruptorales, is proposed containing the family Caldicellulosiruptoraceae, consisting of two genera, Caldicellulosiruptor and Anaerocellum. Furthermore, the order Thermoanaerobacterales also was re-assessed, using 91 genome-sequenced strains, and should now include the family Thermoanaerobacteraceae containing the genera Thermoanaerobacter, Thermoanaerobacterium, Caldanaerobacter, the family Caldanaerobiaceae containing the genus Caldanaerobius, and the family Calorimonaceae containing the genus Calorimonas. A main outcome of ANI/AAI analysis indicates the need to reclassify several previously designated species in the Thermoanaerobacterales and Caldicellulosiruptorales by condensing them into strains of single species. Comparative genomics of carbohydrate-active enzyme inventories suggested differentiating phenotypic features, even among strains of the same species, reflecting available nutrients and ecological roles in their native biotopes.